Этиологические заметки: «История об Иване» - Bogumil Gasanov (Studia mythologica Slavica, 2021)
This article represents research on an obscene Ukrainian folklore text published by Fedor. Vovk. Its possible relation to the verse fairy tale, “Nikita the Tzar, and his Forty Daughters”, by Aleksandr S. Pushkin is considered. The elements of the text are given Slavic folklore parallels, which enables making a conclusion about the clearly folk origin of the creative product. The following question is raised: can the text under research possibly be a distant reverberation of the Slavic etiological myth about how women acquired genitals? While such myths might have pagan roots, a suggestion is made that pagan gods were the prototypes of the main characters in the Ukrainian text. Thus, the text, recorded as an obscene joke, can supplement the collection of aetiological myths and legends about how the original people acquired genitals.